Mitigating cyclophosphamide-associated gonadotoxicity in male Wistar rats: exploring the therapeutic potential of hesperidin - Hari Priya, B.; Ramya, B.; Bora, Swathi; Shivakumar, P.; Rohan, A.; Vagdevi, T.; Amoolya Rao, A. (Frontiers in Veterinary Science, 2024)
Hesperidin plays pivotal role in scavenging ROS, counteracting inflammation and enhancing reproductive parameters. Recent studies have focused on hesperidin supplementation to address ovarian toxicity-induced oxidative stress and infertility in animal models, showcasing promising results such as improved follicular development and hormonal balance, this made hesperidin an attractive target for therapeutic interventions of reproductive studies. Although research on hesperidin's impact on male reproductive toxicity is limited, its potential to improve reproductive parameters justifies further investigation. This underscores the rationale for considering hesperidin as a therapeutic agent for mitigating male reproductive toxicity. Hesperidin, a bioactive flavanone glycoside prevalent in citrus fruits, with remarkable therapeutic properties stands out as a formidable defender against the debilitating reproductive toxicity associated with Cyclophosphamide (CYP) chemotherapy. This study explores the protective potential of hesperidin (HSP@100mg /kg b.wt PO daily) against CYP (@ 40 mg/kg b.wt IP once in a week) induced reproductive toxicity in male Wistar rats.as several studies were documented on single dose toxicity of CYP.in this experiment we chose multidosage drug effects which is more relevant in chemotherapy. Twenty-four rats were divided into four groups: Group 1 (Control), group 2 (CYP-treated), group 3 (HSP-treated) and group 4 (CYP+HSP-treated) for a period of 28 days. The experimental design included assessments of relative testicular weight, semen analysis, testosterone levels, oxidative stress markers, inflammatory cytokines, gross and histopathological changes and immunohistochemical evaluation. Results revealed that CYP administration led to a significant reduction in testicular weight, sperm count, motility and testosterone levels, accompanied by increased oxidative stress and inflammatory response. Hesperidin co-administration demonstrated a protective effect by restoring these parameters to near-normal levels. Histopathological analysis revealed improved testicular architecture in the group 4 compared to group 2. Oxidative stress indices indicated that hesperidin attenuated CYP-induced damage by reducing malondialdehyde levels, enhancing superoxide dismutase activity and maintaining glutathione levels. Similarly, inflammatory cytokine analysis demonstrated hesperidin's anti-inflammatory effects by reducing tumour necrosis factor-alpha (TNF-α) and elevating interleukin-10 (IL-10) levels in the group 4. Immunohistochemical evaluation of nuclear factor-kappa B (NF-κB) revealed increased inflammation in the CYP group, while hesperidin significantly reduced NF-κB expression, suggesting its anti-inflammatory properties.